PREVENTION OF COMPLICATIONS IN CASTRATE-REFRACTORY PROSTATE CANCER PATIENTS WITH BONE METASTASES - K. M. Nushko (Issledovaniâ i Praktika v Medicine, 2015)
Abstract:Prostate cancer (PC) is one of the most urgent problems in modern oncourology. Every year the world is recording more than 900 thousands new cases of prostate cancer. For this reason, the diagnosis and treatment of this disease has recently been given more attention, both abroad and in the Russian Federation. Despite improvements in diagnostic methods and implementation of programs for active detection of the disease in its early stages, the number of patients suffering from advanced forms of prostate cancer remains high. Currently, the main method of treatment in patients with metastatic prostate cancer remains the hormone therapy (HT). Patients with metastatic prostate cancer most frequently have localization of metastatic lesions in the lymph nodes and bones. Frequent localization of metastatic lesions in the bones is due to tumor cell tropism of prostate cancer to the bone. Metastatic bone disease, as well as long-term HT conducted in patients with metastatic prostate cancer, leads to irreversible disruption of bone remodeling, which may be accompanied by osteoporosis and fragility fractures. Bone metastases in patients with PC are the most common cause of complications and significantly impair the quality of life of patients. Therapy underlying the prevention of bone complications can be specific, aimed directly at the tumor tissue and non-specific, to strengthen bones and decrease its resorption processes. The article provides an overview of the literature covering the effectiveness of modern drugs, aimed at non-specific prevention of bone complications in patients with metastatic prostate cancer, such as bisphosphonates, and inhibitors of the ligand RANKL, as well as an overview of studies to assess the effectiveness of domestic analogue zolendronovoy acid preparation Resorba in the prevention of osteoporosis.